Decolonizing Utopia: Indigenous Knowledge and Dystopian Speculative Fiction - Morrison, Mary Irene (eScholarship, University of California, 2017)
In a time of increasing inequality and ecological crisis, it seems more difficult than ever to imagine a more just and equitable world, where humanity's penchant for invention leads to better societies, rather than destroyed environments. Yet it is also conversely more necessary to do so, because such an imagination can become an inspiration for social change. This dissertation first examines how the techno-utopian imagination of even the most politically engaged European/Western science fiction (sf) writers is often problematic, in that it can perpetuate the utopian genre’s centuries-long entanglement with colonialism (dating back to colonial themes in Thomas More’s Utopia [1516]). This entanglement is prevalent for example in the biomedical science fictional imagination of Hollywood, as represented by the film Elysium, which imagines advanced medical technology and a class struggle to distribute it more equitably. Yet the film requires a White Savior (Matt Damon) to lead mostly poor people of color to revolution. Other problematic tropes abound in the genre, including alien Others as Indigenes in a primitive utopia, for example in Avatar. The technoscientific imagination advanced in sf with utopian themes is also coopted by corporations, who use utopian rhetoric to mask exploitation and environmental degradation. For example, Monsanto justifies the use of pesticides that harm people and the environment, by arguing that their advancements will “feed the world” now and into the future. This study then looks at the depiction of Indigenous sciences and knowledges in utopian/dystopian science fiction, in contrast to the techno-utopianism of Western science and science fiction. I study how Gerald Vizenor (Anishinaabe), Nalo Hopkinson (Afro-Caribbean), Thomas King (Cherokee), Larissa Sansour (Palestinian), and others imagine Indigenous philosophies of science, specifically how these approaches can address the world's most pressing problems, such as climate change, biodiversity loss, and inequality — while maintaining healthy and just societies. The fourth chapter for example focuses on Gerald Vizenor’s Heirs of Columbus, a novel featuring a utopian reservation where Indigenous scientists heal genetic trauma resulting from colonialism. I show how Vizenor offers a decolonized view of utopia, through the potential and priorities of an approach to biotechnology informed by Indigenous philosophies.